Mental Health Issues in the COVID-19 Pandemic and Responses in Bangladesh: View Point of Media Reporting - Nabila Ashraf, Mir; Jennings, Hannah; Chakma, Nantu; Farzana, Noshin; Islam, Md. Saimul; Maruf, Toufiq; Uddin, M. M. Jalal; Uddin Ahmed, Helal; McDaid, David; Naheed, Aliya (Frontiers in Public Health, 2021)
Background: The negative impact of COVID-19 on mental health has been reported throughout the world. However, the role played by media in reporting mental health-related issues is not well understood in low-and middle-income countries (LMIC). Here, we examined the reporting of mental health issues during the COVID-19 from the viewpoint of media in Bangladesh and local initiatives undertaken by different organizations to support mental health reported in the media. Methods: We reviewed the articles published in 10 local newspapers, including seven Bangla and three English newspapers, published during the first year of the COVID-19 pandemic. News topics were identified through brainstorming discussions by team members and then searched across online newspapers and portals. Data extrapolated from newspapers were documented in an Excel spreadsheet. A mixed-method approach was used for data analysis with framework analysis for analyzing recurring issues and commonly emerging topics generated from the data and descriptive statistics for quantitative data. Results: Between March 2020 and March 2021, we have identified 201 reports on mental health issues including 45 reports (22.4%) focused on stress due to the associated financial crisis, unemployment, and loneliness,50 reports (24.9%) of 80 apparent suicides linked to family issues, disharmony in conjugal relationships, harassment, sexual violence, emotional breakdown, financial crisis and stigma due to COVID-19. There were 77 reports (38.3%) concerning domestic violence during the pandemic. Around 29 reports (14.4%) referenced actions taken by different organizations to address mental health issues in response to the pandemic in Bangladesh. Conclusion: News coverage has the scope to highlight important issues, such as mental health, during the COVID-19. Policymakers need to be mindful of concerns raised when adopting policies to support essential mental health care in Bangladesh and prevent additional negative consequences that have emerged during the pandemic. Capacity building in the media on the way to report mental health issues during emergency situations could be a useful strategy for more credible reporting on mental health issues during the COVID-19 pandemic. This may help sensitize local organizations to take timely and necessary measures during major health crises to promote and protect mental health in Bangladesh.